La deficiente cobertura del seguro obligatorio de accidentes de tránsito vulnera derechos constitucionales - Menéndez Menéndez, Idder Omar (2015)
The present work of legal research, it takes in order to reform Article 8 of the Statutory Accident Insurance (SOAT) to increase economic amounts of compensation to persons who suffer an accident and are awarded that for this reason they are temporary or permanently unable to live normal lives. This legal research is organized into six chapters. The main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in compliance with the research hypothesis. The refers to the theoretical framework, aspects: historical, doctrinal and legal. The methodology used in the research in question is described, the methods used, types of research, population, sample techniques and instruments used in data collection. The hypothesis is tested through the research results obtained by interviewing authorities located Quevedo , plus surveys of lawyers in free practice , you know as they are violated without any regard to the rights citizens by economic SOAT amounts and not enough to cover medical expenses. The describes the conclusions and recommendations. Finally the discusses the proposal, objectives, description of the ' proposal, beneficiaries and social impact, etc.